Single Dose of the Attention Training Technique Increases Resting Alpha and Beta-Oscillations in Frontoparietal Brain Networks: A Randomized Controlled Comparison - Knowles, Mark M.; Wells, Adrian (Frontiers in Psychology, 2018)
The Attention Training Technique (ATT) was developed with the aim of reducing self-attention and increasing executive control as part of metacognitive therapy. So far there is a paucity of data on the neurophysiological effects of ATT. In the present study we tested for specific effects to determine if attention control components of ATT elicit a specific signature that is different from passive listening. Thirty-six healthy volunteers were randomised to an active (follow instructions) or control (ignore instructions) condition. Resting state EEG was recorded for 3 minutes with eyes open and eyes closed before and after exposure to training, and the power of the theta, alpha, and beta-bands were analysed in frontal, midline, and posterior electrodes. The active ATT condition enhanced alpha and beta-band activity during eyes-open, and frontal alpha during eyes-closed (p’s < 0.005). Frontoparietal changes in Alpha were generally accompanied by changes in Beta in the same brain regions of interest. However, these associations were largely significant in the active ATT rather than the control condition. No between-group differences were observed in the Theta-band. These results suggest a single dose of attention training increases alpha and beta-oscillations in frontoparietal networks. These networks are associated with top-down attentional or executive control.